Individual strategies in project management: models and methods of formation - I. S. Klimenko (Современная наука и инновации)
The article substantiates the need for an individual approach to planning and resource allocation in IT project management. The analysis of the feasibility of using standard models is carried out, approaches to project management are proposed, taking into account the probabilistic nature of the connections of the complex of works, the influence of disturbing influences.